An evaluation of the healthcare costs associated with adverse events in patients with breast cancer. (29th April 2021) - Wang, Lin‐Chien; Chen, Hsuan‐Ming; Chen, Jin‐Hua; Lin, Yi‐Chun; Ko, Yu
Abstract: Objective: Despite the increasing prevalence and costs of breast cancer (BC), little is known about its adverse event (AE)‐related costs in Asia. This study aimed to estimate the healthcare expenditures of AEs in patients with BC in Taiwan. Methods: This is a retrospective claims database analysis. The medical costs associated with BC AEs during the first‐line treatment period were estimated by use of both a matching method and the generalized linear model (GLM). Results: A total of 50, 010 patients diagnosed with breast cancer were identified. Using the case‐control matching method, pneumonitis/pneumonia was the AE associated with the greatest total healthcare costs (NT 66, 889), followed by arthralgia (NT55, 380). In the GLM, the estimated costs ranged from NT 1, 045 for fatigue to NT 116, 652 for left heart failure. Moreover, the estimated total healthcare incremental cost increased with the number of AEs (NT18, 157 for 1 AE, NT33, 827 for 2 AEs, NT39, 052 for 3 AEs, NT53, 348 for 4 AEs, and NT54, 215 for 5 AEs and above). Conclusions: The findings indicate that AEs among patients with BC were associated with a substantial economic burden, and healthcare expenditure rose significantly as the number of AEs increased.